Cushing's syndrome with concurrent use of fluvoxamine, budesonide. Issue 12 (December 2015) - Lam, Y. W. Francis
Abstract : Crohn's disease is a chronic inflammatory bowel disease affecting the small and large intestine, although it also can affect other areas of the gastrointestinal tract, including the mouth, esophagus, and stomach. Currently, there is no pharmacological cure for Crohn's disease, but many medications have been used to reduce symptoms, maintain remission, and prevent relapse. One of these medications is budesonide, an oral glucocorticoid available in a controlled ileal release (CIR) formulation that allows ileocecal localization. In addition, 80 to 90% of budesonide is metabolized by the cytochrome P450 3A4 isoenzyme (CYP3A4) after first passage through the liver, 1 resulting in low systemic bioavailability and minimal suppression of the hypothalamic‐pituitary‐adrenal (HPA) axis.